Beginning theory : an introduction to literary and cultural theory - Barry, Peter (Beginnings (Manchester, England), 2002)
Expanded second edition of this hugely successful introduction to literary theory, a book which has already proven itself as the first port of call for students - Two new chapters added which take account of the changes since the first publication (1995), and all bibliographies have been updated - Given approval by academics and teachers the world over as the clearest and most concise introduction in the area - A consistent bestseller for the last five years